Characterization and Discrimination of Ancient Grains: A Metabolomics Approach - Righetti, Laura; Rubert, Josep; Galaverna, Gianni; Folloni, Silvia; Ranieri, Roberto; Stranska-Zachariasova, Milena; Hajslova, Jana; Dall'Asta, Chiara (International journal of molecular sciences, 2016)
Hulled, or ancient, wheats were the earliest domesticated wheats by mankind and the ancestors of current wheats. Their cultivation drastically decreased during the 1960s; however, the increasing demand for a healthy and equilibrated diet led to rediscovering these grains. Our aim was to use a non-targeted metabolomic approach to discriminate and characterize similarities and differences between ancient Triticum varieties. For this purpose, 77 hulled wheat samples from three different varieties were collected: Garfagnana T. turgidum var. dicoccum L. (emmer), ID331 T. monococcum L. (einkorn) and Rouquin T. spelta L. (spelt). The ultra high performance liquid chromatography coupled to high resolution tandem mass spectrometry (UHPLC-QTOF) metabolomics approach highlighted a pronounced sample clustering according to the wheat variety, with an excellent predictability (Q²), for all the models built. Fifteen metabolites were tentatively identified based on accurate masses, isotopic pattern, and product ion spectra. Among these, alkylresorcinols (ARs) were found to be significantly higher in spelt and emmer, showing different homologue composition. Furthermore, phosphatidylcholines (PC) and lysophosphatidylcholines (lysoPC) levels were higher in einkorn variety. The results obtained in this study confirmed the importance of ARs as markers to distinguish between Triticum species and revealed their values as cultivar markers, being not affected by the environmental influences.
Keywords: vysokoúčinná kapalinová chromatografie; Triticum; metabolomika; Chromatography, High Pressure Liquid; spektrometrie hmotnostní - ionizace laserem za účasti matrice; pšenice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Metabolomics